Study on Aircraft Noise Around Tribhuvan International Airport, Kathmandu, Nepal - Bhattarai, Mohan K.; Sapkota, B. K. (Nepal Journal of Science and Technology, 2015)
Present work was carried out to collect primary data from the field with the help of noise meter and thus spatial anddiurnal variation of background and aircraft noise level was analyzed. Seventeen sampling sites were chosennearby Tribhuwan International Airport (TIA) and air route of aircraft flyover. Noise measurements were carried outunder normal atmospheric environmental condition at temperature ranges from 25°C-30°C excluding rainy andwindy days. Among the sampling sites, the Equivalent Continuous Noise Level (LAeq) of background noise measuredmaximum at Balkumari (73.2 dBA) and minimum at Datidol (49.2 dBA). Noise meter was allowed to record aircraftnoise level when aircraft produced noise greater than background noise level and recorded until it reduced tobackground noise level. The maximum value of aircraft noise level, (LAeq) measured at Gothatar (101.5 dBA) whichlies north east from the TIA and at the same height as the airport ground and minimum at Datidol (63.5 dBA).Toanalyse the spatial variation of aircraft noise of different sampling sites, contour map was plotted with the help oforigin software. The LAeq of more than 60 percent sampling sites fall under the severe noise exposure class (> 75dBA) which causes substantial hearing loss. Implementation of noise control measurement and public awarenessare recommended to control adverse effect of noise pollution. DOI: http://dx.doi.org/10.3126/njst.v15i1.12031 Nepal Journal of Science and Technology Vol. 15, No.1 (2014) 139-144